Pengaruh Live Streaming Shopee terhadap Peningkatan Penjualan Produk Body Care - Nikolas Brian Krisnandi; Ugy Soebiantoro (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aims to analyze the impact of using Live Streaming features on the Shopee platform on increasing sales of body care products. By implementing an effective marketing strategy, products can become more competitive in the market and reach a wider audience, especially among young consumers who are familiar with technology. The research method used is based on the AISAS model (Attention, Interest, Search, Action, Sharing). The results of the study indicate that the implementation of Live Streaming has a significantly positive impact on increasing sales of body care products on the platform. The application of Live Streaming as a marketing strategy carried out by CV Avero Indonesia has proven effective in attracting consumer Attention and driving sales growth. Through Live Streaming, brands can directly interact with their audience, provide real-time product explanations, and answer consumer questions instantly. This not only enhances consumer knowledge and awareness of the products but also builds trust and emotional connections between the brand and consumers. Furthermore, the Live Streaming feature allows brands to present product demonstrations, offer exclusive promotions, and limited-time deals that attract consumers to make purchases. This strategy creates a more interactive and personalized shopping experience, ultimately contributing to increased sales. With the empirical evidence from this study, it can be concluded that Live Streaming is an effective digital marketing strategy for improving the sales performance of body care products on the Shopee platform. Companies like CV Avero Indonesia can continue to optimize this strategy to achieve better results in the future.